Peran Indonesia Pada Konflik Israel – Palestina Melalui Multi-Track Diplomacy - Relycia Solihin; Herlina Juni Risma Saragih; Bayu Setiawan; Pujo Widodo (Universitas Medan Area, 2023)
The Israeli-Palestinian conflict began in the mid-1800s, with European Jewish minorities planning to establish a Jewish homeland. From 2008 to 2022, the Palestinian community who have been victims of the Israeli-Palestinian conflict reached 6,014 people. Indonesia with the majority of its people are Muslims also take a role as a mediator in various international forums, the United Nations and regional, bilateral and multilateral cooperation. The government, supported by various groups, optimizes conflict resolution and overcomes obstacles in efforts to improve Palestinian humanitarian corridors. This study aims to analyze Indonesia's role in the Israeli-Palestinian Conflict through Multi-Track Diplomacy. To approach this problem, theoretical references from Conflict Theory by Johan Galtung, Role Theory by Robert Linton and the Concept of Multi-Track Diplomacy by Louise Diamond &; John McDonald are used. Data was collected by data collection techniques in the form of documentation data and analyzed using the method of Miles, Huberman and Saldana (2014), namely analyzing data by collecting, condensing data, presenting data, and drawing conclusions or verification. By triangulating data sources as a validity test in this study. This study concludes that Indonesia plays a role in the Israeli-Palestinian conflict through nine channels of diplomacy through the government, non-governmental peacemakers, business people, religious activists, funding or financiers, media. The involvement of these various elements, Indonesia's role in the international arena can developed optimally.